Synthesis and biological evaluation of novel selective androgen receptor modulators (SARMs). Part II: Optimization of 4-(pyrrolidin-1-yl)benzonitrile derivatives. Issue 9 (1st May 2017) - Asano, Moriteru; Hitaka, Takenori; Imada, Takashi; Yamada, Masami; Morimoto, Megumi; Shinohara, Hiromi; Hara, Takahito; Yamaoka, Masuo; Santou, Takashi; Nakayama, Masaharu; Imai, Yumi; Habuka, Noriyuki; et al.
Graphical abstract: Abstract: We recently reported a class of novel tissue-selective androgen receptor modulators (SARMs), represented by a naphthalene derivativeA . However, their pharmacokinetic (PK) profiles were poor due to low metabolic stability. To improve the PK profiles, we modified the hydroxypyrrolidine and benzonitrile substituents of 4-(pyrrolidin-1-yl)benzonitrile derivativeB, which had a comparable potency as that of compoundA . This optimization led us to further modifications, which improved metabolic stability while maintaining potent androgen agonistic activity. Among the synthesized compounds, (2 S, 3 S )-2, 3-dimethyl-3-hydroxylpyrrolidine derivative1c exhibited a suitable PK profile and improved metabolic stability. Compound1c demonstrated significant efficacy in levator ani muscle without increasing the weight of the prostate in an in vivo study. In addition, compound1c showed agonistic activity in the CNS, which was detected using sexual behavior induction assay.